Descriptions of the larvae of Huosoma Guan, Dumont, Yu, Han & Vierstraete, 2013 from China (Odonata: Coenagrionidae) - Yang, Guo-Hui; Orr, Albert G.; Zhang, Hao-Miao (Zootaxa, 2022)
The final stadium larvae of Huosoma latiloba (Yu, Yang & Bu, 2008) and Huosoma tinctipenne (McLachlan, 1894) from Yunnan Province, China are described and illustrated for the first time, with diagnostic differences between the two species identified. While no morphological characters separating the adults of this genus, and the closely related western Palaearctic Pyrrhosoma Charpentier, 1840 have been found, the larvae of these two genera do show differences which are discussed here.